Integrating Fraud Diamond Theory and Behavioral Accounting in Analyzing Fraud Driven by Hedonistic Lifestyles in Banking Sector Companies in Indonesia for the Period 2022-2024 - Dhani Wirianto (Future Science, 2025)
This study aims to explore the influence of hedonistic lifestyles on fraud in the Indonesian banking sector, focusing on identifying the relationships between the factors in the Fraud Diamond Theory and fraud. Hedonistic lifestyles, which depict individuals' tendency to pursue personal pleasure without considering long-term consequences, are believed to affect the decision to engage in fraud. This study uses a quantitative design with a survey approach, involving 200 respondents from banks listed on the Indonesia Stock Exchange. The sampling technique employed is purposive sampling, targeting employees and bank management who have knowledge of or direct involvement in fraud practices. Data is collected through questionnaires assessing hedonistic lifestyles, pressure, opportunity, rationalization, ability, and perceptions of fraudulent practices. Data analysis is conducted using multiple linear regression to test the influence of each variable on fraud. The results show that, although there is a relationship between hedonistic lifestyles and fraud, this relationship is weak and not significant. Additionally, the variables in the Fraud Diamond Theory do not show a significant effect on the occurrence of fraud. Practically, these findings provide recommendations for banking institutions to strengthen internal supervision and ethical policies to prevent fraud. From a theoretical perspective, this study contributes to the understanding of the factors influencing fraud in the banking sector, although other factors not tested in this study may have a greater impact.